Re-empowering into voice: experiments in organic community co-production. (2nd October 2020) - Green, Roger; Baker, Chris
Abstract: This article explores and extrapolates an emerging concept within community practice: namely that of organic community co-production . The concept is influenced by previous uses of the term 'organic', specifically as applied by Tönnies in relation to certain types of community, and Gramsci in respect of a concept of leadership. Our development of the term has been generated within the context of reflective practitioner experience, located in a community-led action campaign Voice4Deptford, in South East London. The case study explores the interdisciplinary roots of this form of co-production. It highlights the way that these pre-existing principles and methods have been adapted, reflected upon and improvised in the light of 30 years' grassroots engagement by Green to evolve a bespoke approach that we are proposing to call 'organic community coproduction'. The case study outlines several original dimensions or modalities of community organic co-production including; stepping aside; the academic as a non-expert and giving voice. It unpacks the different elements of impact and transformation, that are consequent upon organic community co-production. These include; evidence of change; working together and community reflective time. The article concludes with a discussion of the issues involved in reframing of local power, the campaigns early successes and its continuing challenges.